3d/4f Coordination Clusters as Cooperative Catalysts for Highly Diastereoselective Michael Addition Reactions - Griffiths,K; Tsipis,AC; Kumar,P; Townrow,OPE; Abdul-Sada,A; Akien,GR; Baldansuren,A; Spivey,AC; Kostakis,GE (INORGANIC CHEMISTRY, 2017)
Michael addition (MA) is one of the most well studied chemical transformation in synthetic chemistry. Here, we report the synthesis and crystal structures of a library of 3d/4f coordination clusters (CCs) formulated as [ZnII2YIII2L4(solv)X(Z)Y] and study their catalytic properties toward the MA of nitrostyrenes with barbituric acid derivatives. Each CC presents two borderline hard/soft Lewis acidic ZnII centers and two hard Lewis acidic YIII centers in a defect dicubane topology that brings the two different metals into a proximity of ∼3.3 Å. Density functional theory computational studies suggest that these tetrametallic CCs dissociate in solution to give two catalytically active dimers, each containing one 3d and one 4f metal that act cooperatively. The mechanism of catalysis has been corroborated via NMR, electron paramagnetic resonance, and UV–vis. The present work demonstrates for the first time the successful use of 3d/4f CCs as efficient and high diastereoselective catalysts in MA reactions.